Enhancement of radiosensitivity of melanoma cells by pegylated gold nanoparticles under irradiation of megavoltage electrons. (1st February 2017) - Mousavi, Mehdi; Nedaei, Hassan Ali; Khoei, Samideh; Eynali, Samira; Khoshgard, Karim; Robatjazi, Mostafa; Iraji Rad, Rasoul
Abstract: Purpose: Gold nanoparticles (GNP) have significant potential as radiosensitizer agents due to their distinctive properties. Several studies have shown that the surface modification of nanoparticles with methyl polyethylene glycol (mPEG) can increase their biocompatibility. However, the present study investigated the radiosensitization effects of mPEG-coated GNP (mPEG-GNP) in B16F10 murine melanoma cells under irradiation of 6 MeV Electron beam. Materials and methods: The synthesized GNP were characterized by UV-Visible spectroscopy, dynamic light scattering, transmission electron microscopy, and zeta potential. Enhancement of radiosensitization was evaluated by the clonogenic assay at different radiation doses of megavoltage electron beams. Results: It was observed that mPEG-GNP with a hydrodynamic size of approximately 50 nm are almost spherical and cellular uptake occurred at all concentrations. Both proliferation efficiency and survival fraction decreased with increasing mPEG-GNP concentration. Furthermore, significant GNP sensitization occurred with a maximum dose enhancement factor of 1.22 at a concentration of 30 μ M. Conclusions: Pegylated-GNP are taken up by B16F10 cancer cells and cause radiosensitization in the presence of 6 MeV electrons. The radiosensitization effects of GNP may probably be due to biological processes. Therefore, the underlying biological mechanisms beyond the physical dose enhancement need to be further clarified.